Stunting Service Management Model in the South-Central Timor Region, East Nusa Tenggara, Indonesia - Sormin, Roslin E. M.; Salesman, Frans; Neolaka, Melkisedek; Toda, Hendrik (European Journal of Applied Sciences, 2024)
South Central Timor is one of the regions with a high prevalence of stunting in Indonesia. The programs and policies that have been carried out have been unable to reduce these health problems effectively. This study resulted in an innovative service model based on intelligent Governance. The design of this study is a sequential explanatory model using the mixed method. The research subjects were 226 respondents and 527 midwives in 27 South Central Timor The results of the analysis found that there are factors that inhibit the management of stunting management services in community health centers in South Central Timor Regency, including (a) tractability of the stunting problems, (b) diversity of group behavior, (c) clarity of policy content, (d) accuracy of allocation of funding sources, (e) socioeconomic conditions of the community and the level of technological advancement, (f) official support for stunting prevention policies. The analysis results have an adjusted R2 (Adjusted R Square) value of 0.436. Service implementation needs to be carried out collaboratively and participatory, especially related to data, policies, budgets, coordination, socialization, and implementation